2017
DOI: 10.1080/14756366.2017.1411350
|View full text |Cite
|
Sign up to set email alerts
|

Plasmatic carbonic anhydrase IX as a diagnostic marker for clear cell renal cell carcinoma

Abstract: Carbonic anhydrase (CA, EC 4.2.1.1) IX is regarded as a tumour hypoxia marker and CA inhibitors have been proposed as a new class of antitumor agents, with one such agent in Phase II clinical trials. The expression of some CAs, in particular the isoforms CA IX and CA XII, has been correlated with tumour aggressiveness and progression in several cancers. The aim of this study was to evaluate the possibility that CA IX could represent a marker related to clear cell Renal Cell Carcinoma (ccRCC). Bcl-2 and Bax, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…All these results indicated that CA IX could be a new therapeutic target to interfere exosome release in hypoxic tumours. Moreover, currently, there is already one CA IX inhibitor (SLC-0111) in Phase Ib/II clinical trials for the treatment of hypoxic, metastatic tumors 45,46,[63][64][65][66][67] . PPIs and CA IX inhibitors are both inhibiting exosome release by regulating the pH of tumour microenvironment.…”
Section: Other Inhibitorsmentioning
confidence: 99%
“…All these results indicated that CA IX could be a new therapeutic target to interfere exosome release in hypoxic tumours. Moreover, currently, there is already one CA IX inhibitor (SLC-0111) in Phase Ib/II clinical trials for the treatment of hypoxic, metastatic tumors 45,46,[63][64][65][66][67] . PPIs and CA IX inhibitors are both inhibiting exosome release by regulating the pH of tumour microenvironment.…”
Section: Other Inhibitorsmentioning
confidence: 99%
“…However, to prevent intracellular H ĂŸ accumulation cancer cells upregulates proton exchangers that extrude protons in excess contributing to acidify extracellular tumour microenvironment 9,11,12 . Among these proton exchangers, a primary role is played by CA IX, an enzyme overexpressed in many types of cancers, including prostate cancer, with the potential to represent both a promising tumour biomarker and a specific target for future cancer therapies 13,[30][31][32][33][37][38][39][40][41]44 . Under the pressure of the acidic microenvironment, CA IX expression and activity are upregulated in both tumour cells 30,44 and the exosomes released extracellularly 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Lucarini et al [ 32 ] evaluated the potential of circulating CAIX to diagnose ccRCC. The concentration of circulating CAIX was significantly higher in patients presenting ccRCC in comparison to controls (benign tumors or healthy subjects).…”
Section: Evidence Synthesismentioning
confidence: 99%